Effect of Adding Caffeine in Tris Extender on Critical Quality Parameters of Cryopreserved Surti Buck Semen - Bhut, Darshita V; Khasatiya, Chandubhai T; Singh, Virendra Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The study was conducted to evaluate the effect of adding caffeine in Tris egg yolk citrate glycerol (TEYCG) extender on critical quality parameters of cryopreserved Surti buck semen. Four mature Surti bucks (aged >1 year) were selected. Total 64 ejaculates were collected @ 2 ejaculates per week/buck over eight weeks period. At every collection, ejaculates of all 4 bucks were pooled and divided into four equal aliquots, diluted with TEYCG extender (having 100 x106 sperms/mL), added with caffeine as 0 mM (T1, control), 1 mM (T2), 3 mM (T3) and 5 mM (T4) in the four aliquots, respectively, and were cryopreserved and stored for 24 h in LN2. Individual sperm motility, viability, morphology and functional membrane integrity of sperms were evaluated at initial, pre-freeze (after equilibration for about 4 h at 4°C) and post-thaw stages. Individual motility, viability, morphologically normal and HOST-reacted sperms decreased significantly (p<0.01) with successive phases of storage. At initial, pre-freeze and post-thaw stage, normal and HOST reacted sperms as well as at pre-freeze and post-thaw stage individual motility and viability were significantly (p<0.01) higher in T2 followed by T3 group than the other groups. It was thus concluded that caffeine supplementation in TEYCG extender has beneficial effect on sperm quality parameters particularly at 1 mM followed by 3 mM as compared to higher (5 mM) caffeine concentration or non-added control.